2019
DOI: 10.1093/advances/nmy097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Milk and Dairy Products on the Prevention of Osteoporosis and Osteoporotic Fractures in Europeans and Non-Hispanic Whites from North America: A Systematic Review and Updated Meta-Analysis

Abstract: Nutrition plays an important role in bone health. The aim of our study was to update the evidence regarding dairy intake, osteoporotic fracture (OF) risk, and prospective bone mass density (BMD) evolution assessed by dual-energy X-ray absorptiometry in Europeans and non-Hispanic whites from North America. A systematic search was conducted in MEDLINE, EMBASE, and Scopus for papers published from 1 January, 2000 to 30 April, 2018. The eligibility criteria were as follows: healthy adults; measurable dairy exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 65 publications
1
52
1
1
Order By: Relevance
“…However, the removal of the previous 2007 dairy food group in the new guidelines remains unclear, even though osteoporosis was one of the health outcomes included in the evidence review for the 2019 guidelines (8) . From the literature, we have seen consistent findings in the effect of dairy products on bone growth in children (20,21) and on lowering the risk of osteoporosis and fractures in older adults (22) . Future work is needed to understand the impact of the removal of dairy recommendations on bone health across different age groups.…”
Section: Discussionsupporting
confidence: 64%
“…However, the removal of the previous 2007 dairy food group in the new guidelines remains unclear, even though osteoporosis was one of the health outcomes included in the evidence review for the 2019 guidelines (8) . From the literature, we have seen consistent findings in the effect of dairy products on bone growth in children (20,21) and on lowering the risk of osteoporosis and fractures in older adults (22) . Future work is needed to understand the impact of the removal of dairy recommendations on bone health across different age groups.…”
Section: Discussionsupporting
confidence: 64%
“…The potential bias by the corporate funding of trials or even speaker fees or travel grants should not be neglected [ 141 , 142 , 143 ]. Of 22 review articles (in English, found in PubMed by the search term “review AND (milk OR dairy) AND (osteoporosis OR fracture)” and limited to those papers with milk, dairy, or other dairy products in the titles published in 2016–2020) published in the past years, 13 papers [ 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 ] were written by at least one author with links to the dairy industry or dairy associations, whereas the authors of nine papers [ 4 , 9 , 10 , 157 , 158 , 159 , 160 , 161 , 162 ] did not report any such conflicts of interest. Although not explored, the proportion of opinion papers, comments, and letters to the editors with conflicts of interest is likely to be higher.…”
Section: Author Autonomy From Dairy Industrymentioning
confidence: 99%
“…Two case-control studies including infants (10-20 months old), children, adolescents, and young adults (up to 20 years) found impaired bone strength and higher fracture risk among those not consuming dairy products [72,73]. However, evidence for a positive association between dairy food consumption and fracture risk reduction is inconsistent, possibly due to methodological differences in study design [74,75]. Issues include lack of consistency in which dairy foods are included in analyses, number, timing, and quality of dietary assessments, and validation of fractures.…”
Section: Impact Of Dairy Matrix On Bone Health and Fracture Risk-epidmentioning
confidence: 99%
“…In the Danish National Diet and Nutrition Survey, the differences in nutrient intake, though not as large, are still present [80]. This may contribute to why results from observational studies using different time points of dietary assessment have inconsistent results [74,81].…”
Section: Impact Of Dairy Matrix On Bone Health and Fracture Risk-epidmentioning
confidence: 99%
See 1 more Smart Citation